Empowering Physics Teachers in Indonesia through DELIVER: A Community-Based Approach to Reduce Student Misconceptions - Achmad Samsudin; Nur Habib Muhammad Iqbal; Nuzulira Janeusse Fratiwi; Nurdini Nurdini; Nanang Dwi Ardi; Andi Suhandi (FOUNDAE (Foundation of Advanced Education), 2025)
Student misconceptions in physics remain a persistent barrier to meaningful learning, often overlooked due to limited teacher training in diagnosis and conceptual remediation. This community service program aimed to enhance the pedagogical capacity of physics teachers in addressing student misconceptions through the DELIVER (Deep Learning-Integrated Verbal Refutation) approach. Implemented using a Community-Based Participatory Research (CBPR) framework, the program involved 237 teachers from various regions in Indonesia, with 69 completing both pre- and post-tests. The training covered deep learning concepts, identification of misconceptions, and practical development of refutation texts. Results indicated significant improvement with normalized gain scores exceeding 0.7 in all concept categories. In addition to cognitive gains, teachers demonstrated reflective shifts in pedagogical awareness regarding the role of misconceptions in learning. A total of 94.12% of participants reported enhanced understanding, and 82.35% expressed readiness to implement the DELIVER approach. In conclusion, the DELIVER approach effectively empowers physics teachers in Indonesia to identify and address student misconceptions, offering a scalable model for professional development in physics and science education. This program contributes to the field by offering a scalable and research-informed model for teacher professional development focused on conceptual change in science education.